The black and the blackness in the traditions of Palma - Adriazola Silva, Juan Carlos (2019)
The topic of black culture in Peru is extensive and complex. The contribution it has given to our miscegenation is not only confined to the biological or racial, but has also high and significant levels that have indelibly marked the entire Peruvian culture, and this is the reason why it cannot be ignored or failed to recognize under any circumstances. To have a bigger picture of the subject, an insight into the background of black slavery in Peru is needed. The aforementioned picture will also help to understand better the Peruvian Traditions in which Don Ricardo Palmaaddresses the issues referred to “the Negro” and “the Negritude”. It should be emphasized that for Palma these issues are not unrelated because of their blood relationship with the black race.